Location identification of line supports using experimental modal analysis - Wu, Lei (2022)
In many engineering applications, line supports are used to reinforce long span structures such as multi-span beams and plates. However, the presence of line supports usually causes local stress concentration. Location identification of line supports is thus indispensable if these stress concentration areas are to be kept off. In this study, to address this issue an easy-to-implement approach was developed using experimental modal analysis (EMA) based on dynamic strain data. A novel index (gradient of strain modal shape vector) that can be calculated by the strain modal shapes of the investigated structure was proposed to assess the rate of change of strain vectors. Simulation results showed that the support locations and stress concentration areas can be easily identified using the plots of calculated index values. In the experimental verification, fiber Bragg grating (FBG) sensors were employed to measure the dynamic responses of a scaled multi-span rectangular plate structure subjected to hammer impact. The measured strain data along a path line on the top surface of the scaled model were used to construct strain modal shapes, further to plot corresponding curve of the proposed index, based on which the locations of line supports were identified successfully. The results showed that the proposed method was effective and convenient for practical applications.